An Analysis of the Policy Environment Surrounding Noncommunicable Diseases Risk Factor Surveillance in Kenya - Rosemary Mamka Anyona; Maximilian de Courten (AIMS Press, 2014)
Kenya is a developing country in sub-Saharan Africa, facing a triple disease burden, with an increase in non-communicable diseases (NCDs); uncontained infectious diseases; coupled with significant morbidity and mortality from environmental causes such as droughts and flooding. The limelight has been on infectious diseases, leaving few resources for NCDs. As NCDs start to gain attention, it is becoming apparent that essential information on their epidemiology and risk factor trends-key in evidence-based decision-making-is lacking. As a consequence, policies have long relied on information derived from unreliable data sources such as vital registries and facility-level data, and unrepresentative data from small-scale clinical and academic research. This study analyzed the health policy aspects of NCD risk factor surveillance in Kenya, describing barriers to the successful design and implementation of an NCD risk factor surveillance system, and suggests a strategy best suited for the Kenyan situation. A review of policy documents and publications was augmented by a field-study consisting of interviews of key informants identified as stakeholders. Findings were analyzed using the Walt and Gilson policy analysis triangle. Findings attest that no population baseline NCD burden or risk factor data was available, with a failed WHO STEPs survey in 2005, to be undertaken in 2013. Despite the continued mention of NCD surveillance and the highlighting of its importance in various policy documents, a related strategy is yet to be established. Hurdles ranged from a lack of political attention for NCDs and competing public interests, to the lack of an evidence-based decision making culture and the impact of aid dependency of health programs. Progress in recognition of NCDs was noted and the international community and civil society's contribution to these achievements documented. While a positive outlook on the future of NCD surveillance were encountered, it is noteworthy that overcoming policy and structural hurdles for continued success is imperative.